ApE, A Plasmid Editor: A Freely Available DNA Manipulation and Visualization Program - Davis, M. Wayne; Jorgensen, Erik M. (Frontiers in Bioinformatics, 2022)
A plasmid Editor (ApE) is a free, multi-platform application for visualizing, designing, and presenting biologically relevant DNA sequences. ApE provides a flexible framework for annotating a sequence manually or using a user-defined library of features. ApE can be used in designing plasmids and other constructs via in silico simulation of cloning methods such as PCR, Gibson assembly, restriction-ligation assembly and Golden Gate assembly. In addition, ApE provides a platform for creating visually appealing linear and circular plasmid maps. It is available for Mac, PC, and Linux-based platforms and can be downloaded at https://jorgensen.biology.utah.edu/wayned/ape/.